If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 + -1x + 36 = x + 45 Reorder the terms: 16 + 36 + -1x = x + 45 Combine like terms: 16 + 36 = 52 52 + -1x = x + 45 Reorder the terms: 52 + -1x = 45 + x Solving 52 + -1x = 45 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 52 + -1x + -1x = 45 + x + -1x Combine like terms: -1x + -1x = -2x 52 + -2x = 45 + x + -1x Combine like terms: x + -1x = 0 52 + -2x = 45 + 0 52 + -2x = 45 Add '-52' to each side of the equation. 52 + -52 + -2x = 45 + -52 Combine like terms: 52 + -52 = 0 0 + -2x = 45 + -52 -2x = 45 + -52 Combine like terms: 45 + -52 = -7 -2x = -7 Divide each side by '-2'. x = 3.5 Simplifying x = 3.5
| 7r+6(r-2)=4r+10(2r+1) | | 45x^2+93x+30= | | 5x+1=7x+10 | | 3x-1=2x-4+2x-3-2 | | 35x^2+38x+8= | | 9x/25=88 | | x-16=36+x+45 | | y^4-13y^2=-36 | | x^3+6x^2-16x= | | 33=3x-28+3x-30+x | | x+16-x=x+36+x-45 | | 4v-2+8v=6 | | -6+v=-9 | | 6(-7)= | | -3z+8+(-22)=-12 | | 9x+25=113 | | 9x+25=63 | | 6=9(h+2) | | -2y+5+5y=19 | | (-6x^8y)(x^7y^3)= | | (-3-2i)-(12-5i)= | | 19-13p=-17p-15 | | z(3z+2)=(z+2)(z+2) | | 1/9x=3 | | 72+4-19c=36 | | 5-1/3(b-6)=4 | | 2x-1=3x+99 | | 26+x=x+23+12-14+x | | 10x-4=20x | | -4/5*5 | | -4.4s-2=6.6s-4.2 | | 1/2(x-4)(x-4)=8 |